The Effect of Performance-Based Budgeting Implementation towards the Institution Performance Accountability (Case Study: Wajo) - Suriani, Seri (Information Management and Business Review, 2015)
This study aimed at finding out empirical evidences whether the application of performance-based budgeting affected the performance accountability of Wajo government, seeing the effects of the application of performance-based budgeting to performance accountability of government agencies using four variables, namely, the budget planning (X1), the implementation of the budget (X2), the budget reporting/accountability (X3), and the performance evaluation (X4). In this study, the samples were 100 people. They are from 33 regional work units (SKPD) which consists of a team of Local Government Budget (TAPD) who involved in formatting the government budgets of Wajo regency. Data were collected through direct observation and survey obtained by distribution of questionnaires to the respondents. This study used multiple linear regression models with software SPSS. The study results showed that the budget planning and the budget reporting / accountability gave positive and significant impacts on performance accountability of government agencies, the implementation of the budget and the performance evaluation. It is shown from the results of multiple linear regression test which showed Y = 7.904 + 0.223 X1 + 0.222 X2 + 1.433 + 0.227 X3 X4. In conclusion, the application of performance-based budgeting gave positive effects on performance accountability of government agencies.